Surgery followed by 585 nm pulsed‐dye laser therapy in the treatment of granuloma faciale - Linh Ha‐Wissel; Lasse Kröger; Ewan A. Langan; Birgit Kahle; Katharina Boch (Wiley, 2023)
Abstract Granuloma faciale is a rare, benign skin disease characterised by solitary or multiple papules, plaques or nodules, most often occurring on the face. The skin disorder is often associated with exacerbations and remissions; spontaneous resolution seldom occurs. The treatment of granuloma faciale is challenging. Various topical and systemic treatments, but also surgical and laser therapies have been administered. A spatially confined thermal destruction of the tissue is achieved by strong absorption of haemoglobin at 585 nm wavelength. Of note, none of the presently available therapeutic interventions are particularly successful. Moreover, Granuloma faciale has the tendency to recur after treatment. Here, we present a male patient with a treatment refractory Granuloma faciale on the right cheek who was successfully treated with the combination of surgery and pulsed‐dye laser therapy. Besides the good aesthetic outcome, remission was maintained after almost 1 year of follow‐up.